Grain-boundary segregation and superior mechanical properties in a multicomponent L12 Ni46.5Co24Fe8Al12.5Ti9 superlattice alloy - Liu, Weihong; Chen, Keyu; Yu, Chunyan (Frontiers in Materials, 2023)
Ni3Al superlattice alloys with the L12 structure have always been pursued due to their attractive high-temperature mechanical properties, however, grain-boundary brittleness and low ductility at the ambient temperature range have greatly restricted their wide applications. In this study, we developed an L12 structure multicomponent Ni46.5Co24Fe8Al12.5Ti9 (at. %) superlattice alloy that notably suppressed the room-temperature intergranular brittleness and exhibited a large tensile elongation of 17.1  5.2% together with a high ultimate tensile strength of 1080.2  57.4 MPa. Multiple microstructural examination reveals an L12 equiaxed-grain microstructure with minor B2 phase. However, co-segregation of Fe and Co atoms and associated reduction or elimination of the L12 chemical order at the grain-boundary regions were characterized, which was proved to be the root cause for the suppression of intergranular brittleness and high tensile ductility. Further theoretical calculations show that alloying of Fe and Co to binary Ni3Al reduced the ordering energy, which promoted intergranular segregation and associated disordering. This observation demonstrated that the elimination or reduction of interfacial chemical order is an effective ductilizing method for superlattice alloys.